2018
DOI: 10.3390/nu10111596
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Profiling of Tumor-Associated Proteins in Human Gastric Cancer Cells Treated with Pectolinarigenin

Abstract: Pectolinarigenin (PEC), a natural flavonoid that is present in citrus fruits, has been reported to exhibit antitumor effects in several cancers. Though the mechanism of PEC-induced cytotoxicity effects has been documented, the proteomic changes that are associated with the cellular response to this flavonoid are poorly understood in gastric cancer cells. In this study, a comparative proteomic analysis was performed to identify proteins associated with PEC-induced cell death in two human gastric cancer cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
(53 reference statements)
4
15
0
Order By: Relevance
“…The synergistic analyses of proteomics data were successful in identifying a unique set of proteins regulated by SCU to induce apoptosis in both treated GC cell lines. Proteins such as PIK3CB, OFD1, CIP2A, BUB1B, ARHGEF2, VCL, EPHB2, IF4G2, CACNA2D1, HIP1R, VAV, and TLR2 have been previously reported to be associated with apoptosis, cell cycle arrest and tumor suppressors induced by another flavonoid in GC cell lines (17). Previous and current data showed that these protein candidates can be altered upon treatment with flavonoids in GC cells.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…The synergistic analyses of proteomics data were successful in identifying a unique set of proteins regulated by SCU to induce apoptosis in both treated GC cell lines. Proteins such as PIK3CB, OFD1, CIP2A, BUB1B, ARHGEF2, VCL, EPHB2, IF4G2, CACNA2D1, HIP1R, VAV, and TLR2 have been previously reported to be associated with apoptosis, cell cycle arrest and tumor suppressors induced by another flavonoid in GC cell lines (17). Previous and current data showed that these protein candidates can be altered upon treatment with flavonoids in GC cells.…”
Section: Discussionmentioning
confidence: 67%
“…GO analysis results showed the greater role of PIK3CB involvement in the maximum category of the biological process as well as being a prominent candidate of all the pathways identified by PANTHER analysis in both cell lines. From our previous study, GC cells treated with Pectolinarigenin, a natural flavonoid, also showed downregulation of PIK3CB protein expression accompanied by a distinct group of cellular functions, including cell growth and proliferation (17). HIP1R is known as an endocytic adaptor with its functional roles in vesicle trafficking and clathrin-mediated endocytosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations